Nurse shark T‐cell receptors employ somatic hypermutation preferentially to alter alpha/delta variable segments associated with alpha constant region. Issue 9 (17th June 2020) - Ott, Jeannine A.; Harrison, Jenna; Flajnik, Martin F.; Criscitiello, Michael F.
Abstract: In addition to canonical TCR and BCR, cartilaginous fish assemble noncanonical TCR that employ various B‐cell components. For example, shark T cells associate alpha (TCR‐α) or delta (TCR‐δ) constant (C) regions with Ig heavy chain (H) variable (V) segments or TCR‐associated Ig‐like V (TAILV) segments to form chimeric IgV‐TCR, and combine TCRδC with both Ig‐like and TCR‐like V segments to form the doubly rearranging NAR‐TCR. Activation‐induced (cytidine) deaminase‐catalyzed somatic hypermutation (SHM), typically used for B‐cell affinity maturation, also is used by TCR‐α during selection in the shark thymus presumably to salvage failing receptors. Here, we found that the use of SHM by nurse shark TCR varies depending on the particular V segment or C region used. First, SHM significantly alters alpha/delta V (TCRαδV) segments using TCR αC but not δC. Second, mutation to IgHV segments associated with TCR δC was reduced compared to mutation to TCR αδV associated with TCR αC. Mutation was present but limited in V segments of all other TCR chains including NAR‐TCR. Unexpectedly, we found preferential rearrangement of the noncanonical IgHV‐TCRδC over canonical TCR αδV‐TCRδC receptors. The differential use of SHM may reveal how activation‐induced (cytidine) deaminase targets V regions. Abstract : Somatic hypermutation targets nurse shark T‐cell receptors (TCR) differentially based on the variable (V) segment and the associated constant (C) region incorporated into a transcript. We observed the greatest mutation to αδV segments associated with αC (but not δC), suggesting that the C region is important for AID targeting.